Perlindungan Hukum Nasabah terhadap Kerugian Akibat Pengalihan Asset Berdasarkan Prinsip Penyingkapan Tabir Perseroan ((Piercing The Corporate Veil) dalam kaitannya dengan Pertanggung Jawaban Komisaris ( Studi PT. Bank Century.,Tbk) - Gios Adhyaksa (UNIFIKASI : Jurnal Ilmu Hukum, 2015)
Against a Limited Company in Banking in accordance with the form of business entity and legal entity that is the Law No.. 40 of 2007 on Limited Liability Company and the Law No.. 10 of 1998 concerning Banking can be used as a basis for assessing the application of the principle of legality Piercing The Corporate Veil in the case of PT. Bank Century Tbk. and organs Piercing The Corporate Veil aims for the creation of wealth and prosperity not only for organ (direksi, shareholders, and the commissioner) of the company, but also for all stakeholders (customers, investors, creditors, employees). After reviewing the case of PT. Bank Century Tbk is known that there are some legal issues that occurred and resulted in the company and stakeholders at a disadvantage, in which the organ PT. Bank Century Tbk together misusing authority and take advantage of banks to personal self-interest. The problems that can be identified are as follows: How does the function and position of commissioner of PT Bank Century Tbk in order to protect customer funds users, the commissioners responsibility for customer losses by shifting assets on the basis of the company's attitude veil (piercing the corporate veil), the effort commissioners should be done along with other directors to deal with customer losses caused by the transfer of assets. Results of research that has been done shows that PT. Bank Century Tbk proven to have committed an unlawful act of the early establishment of PT. Bank Century Tbk. Efforts should be made in the application of the responsibility to the stakeholders, namely with the implementation of the principle of piercing the corporate veil. The principle of piercing the corporate veil is one of the efforts of the Government to provide justice to the stakeholders, which saw the implementation of the responsibility of the company personally organ came to abolish private property with limited liability of the organ (limited liability). This is a descriptive analytical study aimed to obtain a thorough and systematic application of the principle of piercing the corporate veil of PT Bank Century Tbk associated with the statutory provisions. The method used is normative, the research focuses on the study of literature in the form of secondary data to determine how the application of the principle of piercing the corporate veil in PT. Bank Century Tbk.Keywords : Piercing The Corporate Veil, Bank, Company Limited.